Digital political discourse in #nazarpemilu unique hashtag on X/Twitter in the 2024 Indonesian presidential election - Dudi Iskandar; Didik Hariyadi Raharjo; Ngimadudin Ngimadudin; Liliyana Liliyana; Tia Nurapriyanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
#nazarpemilu on X/Twitter was a unique digital political reality during the 2024 Indonesian presidential election. It stood out as the only political hashtag that had practical consequences in the real world. On January 6, 2024, there were 49,562 mentions of #nazarpemilu on X/Twitter. The movement involved 6,432 accounts. This study aimed to describe and critique the construction of digital political reality on #nazarpemilu. This research uses a qualitative approach with a critical discourse analysis method.Through analyzing #nazarpemilu documents, conducting in-depth interviews with account owners, utilizing library data, and exploring intertextuality, it was discovered that social media acted as a public platform for expressing political aspirations in the face of inactive state institutions. #nazarpemilu represented a manifestation of despair against the inefficacy of formal state institutions, supporting candidates who shared similar values and opposing those who lacked integrity or violated the constitution. The research concluded that the dynamics of social media showcased a wave of positive, creative, and constructive energy that transcended into the physical realm. The readiness to embrace differing opinions online and offline led to many ideas and creativity, as evidenced by #nazarpemilu. The results of the study show that hashtags on X/Twitter are an arena for discourse battles to thwart candidates in political contests. Furthermore, social media goes beyond its original nature and function. It has turned into a political action that mobilizes citizens.